Size-conditioned mandatory capital adequacy disclosure and bank intermediation - Zelenyuk, N.; Faff, R.; Pathan, Md Shams Tabrize (WILEY, 2019)
© 2019 Accounting and Finance Association of Australia and New Zealand We add to the literature on the real effects of macroprudential regulation by investigating the novel link between a mandatory capital adequacy disclosure and bank intermediation. The mandatory disclosure stems from the Federal Reserve regulation change of 2013 and leads to identification of bank intermediation effects with treatment methods. A combined empirical strategy of difference-in-differences and regression discontinuity design point to economically significant evidence for the reduction of both lending and on-balance sheet liquidity creation, for banks that disclose their capital adequacy as prescribed by the regulation.